Impact of Human Resource Management Practices on Employee Productivity in Hospital Xyz in Jawa Barat: A Multivariate Analysis of Recruitment, Training, And Compensation - Prasetyo, Arif Tri; Reynaldo, Giovani; Sorongku, Ronald (Jurnal Manajemen (Edisi Elektronik), 2025)
This study explores the impact of Human Resource Management (HRM) practices on employee productivity within hospital settings. The HRM dimensions examined include recruitment and selection, training and development, as well as compensation and rewards. Us-ing Structural Equation Modeling (SEM) with the SmartPLS applica-tion, this research analyzes the relationships among these variables. Data were collected from hospital employees across West Java. The findings reveal that all three HRM practices have a meaningful in-fluence on employee productivity. This indicates that well-structured HRM strategies particularly those focused on equitable compensation and continuous employee development play a vital role in enhancing workforce performance in hospitals. The results underscore the importance of effective HRM in supporting organiza-tional outcomes. Additionally, the study offers valuable insights for hospital management and encourages future research to investigate other relevant factors that may contribute to improved employee productivity in healthcare institutions.